Effect of Supplementation Purslane (Portulaca oleracea) as a Source of Alpha-Linolenic Acid on Production Performance and Physical Quality of Egg of Laying Hens - Kartikasari, Lilik; Nuhriawangsa, Adi Magna Patriadi; Hertanto, Bayu Setya; Swastike, Winny (ANIMAL PRODUCTION, 2015)
The aim of the study was to evaluate the effects of inclusion plant source of n 3 fat in the form of alpha-linolenic acid (ALA, 18:3n-3) on the diets of layers on production performance and physical quality of eggs. A total of Â 125 Hy-Line Brown hens (38 weeks old) were placed at individual cages and assigned to five dietary treatments. The dietary treatments were supplemented with 0, 1.5, 3.0, 4.5 and 6.0% purslane meal. Laying hens were fed for five weeks following a seven day adaptation period. Water and feed were provided ad libitum. Feed intake (FI) measured weekly and feed consumption ratio (FCR) was calculated at the end of the trial. A total of 25 egg yolk samples of day 35 (n = 5 egg yolks for each treatment) were collected to analyse physical quality of eggs. The data were analyzed using Analysis of Variance (ANOVA). Differences between treatment means were further analyzed using Duncans New Multiple Range Test (DMRT). Results showed that the incorporation of plants rich in ALA did not modify FI, FCR, and egg production. Supplementation of purslane meal in the diets had no effect on physical quality of eggs, including egg weight, yolk weight, albumen index, yolk index and Haugh Unit (HU). The average of egg weight and yolk weight were 60,5 and 15.3 g, respectively. Diet containing purslane meal increased yolk colour. In conclusion, laying hens that fed diet supplemented with purslane meal rich in ALA improved yolk colour and did not change the production performance of the laying hens or the qualities of the eggs.